Pendampingan Peningkatan Media Pemasaran dan Pengelolaan Manajemen Keungan Usaha Mikro Kecil dan Menengah “UMKM Sempulur” - Estuning Dewi Hapsari; Ilham Jua Marimba; Juanesmalisa Juanesmalisa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Micro, Small and Medium Enterprises (MSMEs) have an important role in advancing and improving the economy. Sempulur is one of the MSMEs located on Jalan Pelita Tama No. 2b, Rejomulyo Village, Kartoharjo District, Madiun City. This assistance aims to help the problems faced by Sempulur MSMEs. The service methods used are observation, information collection, problem mapping, implementation of mentoring activities, and problem evaluation. In this activity, the results of MSMEs Sempulur can be seen in the form of increasing marketing media in the form of understanding of social media so that it can improve product marketing. Planned and efficient financial management. For the government, it is better to provide individual guidance and mentoring to MSMEs to assist in business planning, management, and development.